A GENDER-BASED ANALYSIS OF KURIKULUM MERDEKA: (An Epistemological Review) - Siti Nur Maela; Abdul Wachid Bambang Suharto (IJouGS: Indonesian Journal of Gender Studies, 2026)
This research was born from the author's concerns about various cases of sexual violence and bullying in the world of education. For example, there were reports of 202 students being victims of sexual violence in the school environment. With the emergence of cases like this, it is necessary to make efforts to analyze this, one of which is through implementing a gender-based curriculum, so the idea of a gender perspective independent curriculum analysis study in epistemological review emerges. This research aims to 1) analyze how essential it is to implement gender-based values in the independent curriculum in schools and 2) how the review of epistemological philosophy responds to the independent curriculum with a gender perspective. This journal study uses library research by collecting various data sourced from books, journals, articles and certain writings, one of which is data sources related to the curriculum in Indonesia or references with similar discussions to obtain valid and actual data. After carrying out the analysis, it was found that the independent curriculum really includes the values of gender equality, including the independent curriculum with a differentiated approach, the P5 project, the Strengthening Pancasila Student Profile Project and the national assessment of education reports on the Gender Equality Climate assessment. From an epistemological perspective, a gender perspective-free curriculum already represents a spirit that is in line with the constructivist learning paradigm. From the results of this research, it is hoped that a curriculum with a gender perspective can be implemented on a massive scale to create a more gender-equitable educational environment.